Guessing Meaning From Word Sounds of Unfamiliar Languages: A Cross-Cultural Sound Symbolism Study - D’Anselmo, Anita; Prete, Giulia; Zdybek, Przemysław; Tommasi, Luca; Brancucci, Alfredo (Frontiers in Psychology, 2019)
Sound symbolism referred to a non-arbitrary relationship between the sound of a word and its meaning. With the aim to better investigate this relationship by using natural languages, in the present cross-linguistic study 215 Italian and Polish participants were asked to listen to words pronounced in 4 unknown non-indo-European languages (Finnish, Japanese, Swahili, Tamil) and to try to guess the correct meaning of each word, by choosing among 3 alternatives visualized on a computer screen. The alternatives were presented in the mother tongue of participants. Three different word categories were presented: nouns, verbs and adjectives. A first overall analysis confirmed a semantic role of sound symbols, the performance of participants being higher than expected by chance. When analyzed separately for each language and for each word category, the results were significant for Finnish and Japanese, whereas the recognition rate was not significantly better than chance for Swahili and Tamil. Results were significant for nouns and verbs, but not for adjectives. We confirm the existence of sound symbolic processing in natural unknown languages, and we speculate that some possible difference in the iconicity of the languages could be the basis for the difference we found. Importantly, the evidence that there were no differences between Italian and Polish participants allows us to conclude that the sound symbolism is independent of the mother tongue of the listener.